2022
DOI: 10.3389/fonc.2022.881665
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome After Pencil Beam Scanning Proton Therapy of Patients With Non-Metastatic Malignant and Benign Peripheral Nerve Sheath Tumors

Abstract: ObjectivePeripheral nerve sheath tumors (PNSTs) commonly arise from peripheral nerve roots and grow locally invasive. Malignant PNSTs (mPNSTs) represent aggressive sarcomas of neural origin that can originate from PNSTs. Radiation therapy is commonly used as part of the required multimodal treatment. However, both entities tend to occur early in life and are associated with the genetic disorder neurofibromatosis type 1 (NF-1), which is known to cause increased radiosensitivity. Pencil beam scanning proton ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The study demonstrated good tolerance to hadron therapy treatment, with only five cases of grade 3 acute toxicities and two cases of grade 3 late toxicities. The authors highlighted the relevance of dose sparing to organs at risk achieved with PBT, especially considering the frequent association of this pathology with neurofibromatosis type 1 (NF-1), which caused a high risk of radiation side effects, as well as the development of secondary tumors [50].…”
Section: Proton Beam Therapy In Pediatric Nrstsmentioning
confidence: 99%
“…The study demonstrated good tolerance to hadron therapy treatment, with only five cases of grade 3 acute toxicities and two cases of grade 3 late toxicities. The authors highlighted the relevance of dose sparing to organs at risk achieved with PBT, especially considering the frequent association of this pathology with neurofibromatosis type 1 (NF-1), which caused a high risk of radiation side effects, as well as the development of secondary tumors [50].…”
Section: Proton Beam Therapy In Pediatric Nrstsmentioning
confidence: 99%